(untitled) (Linguostylistic Studies, 2017)
Peculiarities of football vocabulary in the specific sphere of functioning are analyzed in the article. The football lexicon is divided into several taxonomic ranks: 1) terms of football sphere, 2) extradisciplinary terminological units, 3) terminologized common lexical units, 4) nomenclature, 5) professionalisms, professional jargon. It has been revealed that sport journalists use metaphorical set expressions and utterances in commenting the football matches, news releases and programs. These expressions contribute to the formation of the semantic field of the concept football. Much of the football sphere information is presented on the football sites. Football terminology and nomenclature are most widely used in this field of the information space. Jargons are most frequent in the blogs of the authors, chat rooms, on the football forums. In the course of analysis it has been found out that football vocabulary is characterized by a high degree of expressiveness, emotionality, creation of imagery.